Pickling Behaviour of 2205 Duplex Stainless Steel Hot-Rolled Strips in Sulfuric Acid Electrolytes - Jianguo Peng; Moucheng Li (Advances in Materials Science and Engineering)
Pickling behaviour of the oxide layer on hot-rolled 2205 duplex stainless steel (DSS) was studied in H2SO4 solutions with electrolytic workstation. The pickling rate at 75°C increases slightly with the H2SO4 concentration from 100 to 250 g L−1 but increases markedly as the concentration is higher than 250 g L−1. The solution temperature greatly accelerates the pickling rate. Fe3+ ion is an effective oxidant, which shows stronger inhibitive effect. The rotating disk electrode was used to simulate the moving state of steel strips in practice. The movement with the speed from 0 to 20 m min−1 results in weak acceleration effect on the pickling process. Under dynamic conditions, the pickling rate increases noticeably with changing the pulse current density from 0 to 0.2 A cm−2. The industrial pickling efficiency of 2205 DSS hot-rolled strips increases from 5–8 m/min to 15–18 m/min. The surface quality is improved.